A study of Aural Skill in Basic Chord Structure in Music Students of Phitsanulok Province - บุญรอด วิชญ์ (Journal of Fine and Applied Arts Khon Kaen University, 2019)
This study employed mixed-research methodology with the purposes of discovering the aural skill of for basic chords and the ways to encourage learning the basic-chords aural skill of the Western Music Major students, Phitsanulok Province. The participants of this study were 48 second-year students, including 19 from Western Music Major, Department of Music, Faculty of Humanities, Naresuan University, and 29 from Western Music Major, Faculty of Humanities and Social Sciences, Pibulsongkram Rajabhat University. The criteria for volunteering were that the students must have passed a course from their university’s curriculum, which included the context and practical lesson about the chord aural skill; and they must have been registered as a second-year student of Naresuan University and Pibulsongkram Rajabhat University of academic year 2018. The participants will be called “Volunteers” in this study. The researcher has divided the research study into 2 phrases. Phrase I, the researcher has used the aural skill examination form which is the tool to measure the basic-chord aural skill of the volunteers. Phrase II, the researcher has applied qualitative research method, such as group discussion to discover the way to encourage the volunteers’ basic-chord aural skill. The result of the basic-chord aural skill of the 48 Western Music students in Phitsanulok was found that 52.09 percentage of the volunteers had the basic chord aural skill in improvement needed level. This was in a high number comparing to the rest amount of the students. Therefore, there should be the ways to improve the basic-chord aural skill. According to the study of the ways to encourage learning the basic-chord aural skill, it was found that the instructors should understand the diversity of the students’ capability. They should create more attractive ways to make the students more interested in practicing. For the teaching methods, the instructors should improve the teaching methods to be more appropriate and encouraging the students to be able to learn and analyze the contexts by themselves. For the teaching supporters, it was found that the teaching media were inadequate. There should be the development of teaching media or more up-todate innovation for the easier access and self-learning of the students.